The Challenges of Implementing E-government in the Public Sector: A Case Study on The Gambia - Musa M Juwara; Kerkulah P Nyeleker (Journal of Governance Innovation, 2025)
In recent years, e-government has emerged in public sectors as a tool between governments and citizens for efficient service delivery and governance transparency. However, there are still challenges, especially in developing countries with limited human and financial resources. This study examines the challenges of implementing e-government in developing countries using The Gambia as a case, where e-government is still at its early stage of development. The research applied a qualitative case study approach and relied heavily on secondary data from journals, newspapers, reports from government agencies, etc. The data were analysed interactively using the NVivo 15 software, guided by the Challenges Framework of E-government Implementation theory developed by Odat. The findings of this study revealed that e-government enhances effective service delivery, improves transparency and accountability, reduces corruption, promotes inclusivity, and fosters citizens’ participation. However, with all these benefits, implementation still faces massive challenges such as (a) IT infrastructure with high skill shortage among government employees and citizens; (b) managerial issues, where there is limited internal collaboration with the relevant stakeholders; and (c) digital culture characterised by limited awareness, unequal internet accessibility and affordability, and with little confidence or trust in government services. This study will contribute to the existing academic knowledge on e-government implementation in developing countries and public service innovation in general.